2008
DOI: 10.1021/bp049831p
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an Anti-Apoptotic Protein Isolated from Lonomia obliqua Hemolymph

Abstract: Previously it was reported that supplementation of insect cell culture with Lonomia obliqua hemolymph could extend culture longevity (Maranga et al. Biotechnol. Prog. 2003, 19, 58-63). In this work the anti-apoptotic properties of this hemolymph in Spodoptera frugiperda (Sf-9) cell culture were investigated. The presence or absence of apoptotic cells was characterized by light microscopy, flow cytometry, and agarose gel electrophoresis. Hemolymph was fractionated by several ion exchange and gel filtration chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 23 publications
0
41
0
7
Order By: Relevance
“…This effect was attributed to the presence of three factors with different activities: a potential antiapoptotic factor, a growthpromoting factor, and an enzyme that hydrolyzes sucrose. Furthermore, an antiapoptotic protein of 51 kDa was purified from L. obliqua hemolymph [36]. This protein was able to prevent apoptosis in Sf-9 cell culture induced by nutrient deprivation and by Actinomycin D. Later reports [37,38] described in the hemolymph a potent antiviral activity against human virus.…”
Section: Losac: Functional Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was attributed to the presence of three factors with different activities: a potential antiapoptotic factor, a growthpromoting factor, and an enzyme that hydrolyzes sucrose. Furthermore, an antiapoptotic protein of 51 kDa was purified from L. obliqua hemolymph [36]. This protein was able to prevent apoptosis in Sf-9 cell culture induced by nutrient deprivation and by Actinomycin D. Later reports [37,38] described in the hemolymph a potent antiviral activity against human virus.…”
Section: Losac: Functional Characterizationmentioning
confidence: 99%
“…The α-helices and β-sheets observed in Hyalophora cecropia hemolin (Protein Data Bank code 1BIH) and Losac are shaded in light and dark gray, respectively. Previously it was predicted that hemolin contain conserved regions and motifs (28,36). Conserved motifs are shown inside boxes according to the domain they belong.…”
Section: Molecular Cloning and Heterologous Expression Of Losacmentioning
confidence: 99%
“…A more recent epigenetic role for parthenolide in cancer has been shown, by specifically inhibiting DNA methyltransferase 1 (DNMT1) and histone deacetylase 1 (HDAC1) activities, leading to DNA hypomethylation in vitro and in vivo (Liu et al, 2009;Ghantous et al, 2010). Also, the ability of plant secondary metabolites, such as vitamins, isothiocyanates, quercetin, catechins, resveratrol, epigallocatechin-3-gallate (EGCG), genistein and curcumin, to prevent and/or inhibit tumor growth, either alone or in combination with other anticancer drugs and/or other phytochemicals has been documented (de Souza et al, 2005;de Souza et al, 2006;Hemalswarya & Doble, 2006;de Souza Queiroz et al, 2007;Newman & Cragg, 2007;de Fátima et al, 2008a;Bailly, 2009;Camargo et al, 2011). In this respect, all-trans-retinoic acid (vitamin A) is now widely used for the treatment of myeloid leukemia (Sanz & Lo-Coco, 2011) and vitamin D is in clinical trial for this disease (Trump et al, 2006).…”
Section: Plants As a Valuable Source Of Anticancer Drugsmentioning
confidence: 99%
“…Some studies have demonstrated the presence of pharmacologically active substances in hemolymphs from insects (Shiotsuki et al 2000;Yamamoto et al 1999;Guerrero et al 1990;Jiang et al 1999;Rosenfeld and Vanderberg 1998;Hamdaoui et al 1998;Maranga et al 2003;Lin et al 1998;Zhu et al 2000;Souza et al 2005). The supplementation of cell cultures with hemolymph proteins had a positive effect on viral replication (Rhee and Park 2000), and recombinant protein production (Woo et al 1997).…”
Section: Introductionmentioning
confidence: 99%